Firms' proactive contribution towards carbon neutrality - LEE, Joon-Young (KDI School, 2023)
Proactive contribution towards carbon neutrality by heavy carbon-footprint firms is one of the challenges the global community is facing. Consequently, there has been high scholarly interest in exploring firms’ carbon performance and its association with various company aspects. This exploratory research utilizes ‘investments in sustainability’ as a proxy for carbon performance and empirically examines its relationship with environmental litigation and market share — both subjects of extensive academic inquiry. This paper uses a sample of carbon-intensive firms operating in the United States over the period of 2013 to 2021. The findings indicate a lack of statistical significance for both environmental litigation and market share in their relationship with ‘investments in sustainability.’
Thesis(Master) -- KDI School: Master of Development Policy, 2023
Keywords: Carbon dioxide mitigation--United States; Greenhouse gases--Environmental aspects--United States; Renewable energy resources